Green Banking Disclosure: The Effect of Company Size, Board of Directors’ Age, and Profitability on Islamic Commercial Banks in Indonesia - Komariah, Rizka; Sari, Sinta Ayu Purnama (MALIA: Journal of Islamic Banking and Finance, 2025)
Despite the growing emphasis on sustainability, green banking disclosure in Islamic commercial banks remains underexplored, particularly regarding the role of board demographics. This study aims to examine the influence of company size, age of the board of directors, and profitability on green banking disclosure among Islamic banks in Indonesia. Using a quantitative approach, secondary data from annual and sustainability reports of five Islamic commercial banks were analyzed over the period 2021–2023. Panel data regression with the fixed effect model was employed using EViews 12. The findings reveal that company size and board age have a positive and significant effect on green banking disclosure, suggesting that larger institutions and more mature leadership contribute to greater transparency in environmental practices. However, profitability does not show a significant relationship, indicating that financial performance alone may not drive sustainable reporting initiatives. These results reinforce the relevance of stakeholder theory, where institutional characteristics influence environmental accountability. The study highlights the need for regulatory encouragement beyond voluntary disclosure. It is recommended that regulators and banking associations promote standardized green disclosure frameworks and include sustainability training for board members to enhance environmental governance within Islamic financial institutions.